2001
DOI: 10.1007/s100960100548
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Procalcitonin Serum Level for the Diagnosis of Bacteremia

Abstract: The predictive value of procalcitonin serum levels to detect or rule out bacteremia was investigated prospectively in a case-control study with 200 hospitalized adults from whom blood samples were taken for culture. Fifty bacteremic patients (cases) had higher procalcitonin serum levels than the 150 controls with sterile blood cultures (11.7 vs. 0.7 ng/ml; P=0.0001), a difference that remained significant after controlling for potential confounders in multivariate analysis. At cut-off values of 0.5 and 0.2 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 15 publications
(22 reference statements)
4
46
1
5
Order By: Relevance
“…However, the roles of PCT and the origin of its production, as well as the 25 showed that PCT determination in adult patients with sepsis had a lower specificity (79%) and higher negative predictive value (78%), but lower sensitivity (60%) and positive predictive value (61%) than in our study, as above. The study by Liaudat et al 26 intended to evaluate PCT concentration as an early predictive marker of bacteremia. In their hospital, where the prevalence of bacteremia was 8%, they found that PCT evaluation had a negative predictive value of 96%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the roles of PCT and the origin of its production, as well as the 25 showed that PCT determination in adult patients with sepsis had a lower specificity (79%) and higher negative predictive value (78%), but lower sensitivity (60%) and positive predictive value (61%) than in our study, as above. The study by Liaudat et al 26 intended to evaluate PCT concentration as an early predictive marker of bacteremia. In their hospital, where the prevalence of bacteremia was 8%, they found that PCT evaluation had a negative predictive value of 96%.…”
Section: Discussionmentioning
confidence: 99%
“…20 Even though, for the purpose of BSI management, PCT has been found superior to conventional diagnostic methods in terms of test speed and accuracy in several studies, there is still no general consensus in this regard or in suggesting a widely accepted cut-off value despite the availability of several case-control studies and large meta-analyses. [9][10][11][12][13][14] For example, in a study by Liaudat et al 21 that included 50 hospitalized bacteremic patients and 150 controls, at cut-off values of 0.5 and 0.2 ng/mL the sensitivity and specificity of PCT to detect BSIs were 56-92% and 83-43%, respectively. Sudhir et al 1 included 100 patients with sepsis in their study and reported a high sensitivity value (94%) for serum PCT to detect BSIs.…”
Section: Discussionmentioning
confidence: 99%
“…While the serum PCT concentration is below 0.5 ng/ml in healthy individuals, PCT levels rise above 10 ng/ml in sepsis [1,2,6]. Accordingly, PCT is a well-established diagnostic parameter with a high predictive value to detect or rule out bacteremia and sepsis [1,2,3,6,8,10]. In addition, two contemporary studies have shown a high sensitivity and specificity of serum PCT in adults for the laboratory diagnosis of bacterial meningitis [4,16].…”
Section: Sirmentioning
confidence: 96%